2011
DOI: 10.4103/0253-7613.84974
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of an aphrodisiac herb Tribulus terrestris Linn on cadmium-induced testicular damage

Abstract: Aim:The aim of the present study was to investigate whether Tribulus terrestris Linn (TT) could protect the cadmium (Cd)-induced testicular tissue peroxidation in rats and to explore the underlying mechanism of the same.Materials and Methods:In vitro and in vivo studies were conducted to know the protective effect of ethanolic extract of TT (eTT) in Cd toxicity. In in vitro studies, total antioxidant and ferrous metal ion chelating activity of TT was studied. In vivo studies were conducted in rats. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…This protective effect seemed to be a dose-dependent. These findings were partially in agreement with those previously reported [ 8 - 11 , 14 , 29 , 30 ]. The previous authors concluded that T. terrestris plant acts as a powerful aphrodisiac in rats, mice and humans; improves semen quality and quantity and increases weights of the testis and epididymis.…”
Section: Disscusionsupporting
confidence: 94%
See 1 more Smart Citation
“…This protective effect seemed to be a dose-dependent. These findings were partially in agreement with those previously reported [ 8 - 11 , 14 , 29 , 30 ]. The previous authors concluded that T. terrestris plant acts as a powerful aphrodisiac in rats, mice and humans; improves semen quality and quantity and increases weights of the testis and epididymis.…”
Section: Disscusionsupporting
confidence: 94%
“…Tribulus terrestris plant, popularly known as puncture vine, is a perennial creeping herb with a worldwide distribution. Since ancient times, T. terrestris has a long history as a powerful aphrodisiac [ 8 , 9 ]. In traditional medicine, T. terrestris roots are used for treating male infertility [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study suggest that administration of the fruit extract of TT (200 mg/kg BW/day) in mice prevents the free radical generation caused by MTZ and hence oxidative stress, as evidenced by restoring the levels of antioxidative enzymes and LPO to the control values. Protective effects of TT by inhibiting the free radicals generation against cadmium[ 7 ] and cypermethrin[ 8 ]-induced testicular damage have been reported in the rat. The whole plant extract of TT is reported to exhibit antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the involvement of TT in the improvement of male sexual dysfunctions is well-established. TT is reported to have a protective effect against cadmium[ 7 ] and cypermethrin[ 8 ]-induced testicular injury in the rat. Hence, based on the aphrodisiac and antioxidant properties of TT, the present study has been carried out with the objective to access the potentiality of the fruit extract of this plant against MTZ-induced changes in the testicular oxidative stress, functional markers, spermatogenesis, and the sperm count.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, TT exerted a protective effect against testicular damage induced by cadmium in rats, and this effect seems to be mediated by its antioxidant action and it also stimulates the production of testosterone from the Leydig cells [ 14 ]. Other studies show that TT presented an antioxidant and protective effect in rats with heart disease and diabetes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%